Variation of the molecular cloud lifecycle across the nearby galaxy population - Kim, Jaeyeon; Chevance, Mélanie; Kruijssen, Diederik; Leroy, Adam K. (Proceedings of the International Astronomical Union, 2023)
The processes of star formation and feedback take place on the scales of giant molecular clouds (GMCs; ~ 100 pc) within galaxies and play a major role in governing galaxy evolution. By applying a robust statistical method to PHANGS observations, we systematically measure the evolutionary timeline from molecular clouds to exposed young stellar regions, across an unprecedented sample of 54 galaxies. These timescales depend on galaxy environment, revealing the role of galactic-scale dynamical processes in the small-scale GMC evolution. Furthermore, in the 5 nearest galaxies of our sample, we have refined the GMC timeline further and established the duration of the heavily obscured phase, using 24 μm emission. These results represent a major first step towards a comprehensive picture of cloud assembly and feedback, which will be extended to 19 more galaxies with our ongoing JWST Large Program.
Elektronische Reproduktion der Druck-Ausgabe
Online publiziert: 9. Juni 2023
Gesehen am 20.01.2025